Defining, Designing, and Evaluating Civic Values in Human Computationand Collective Action Systems - Matias, J.; Geiger, Stuart (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Collective action is often described in terms of the relationships, learning, principled processes, and community capacities it fosters. Despite this, human computation and collective action systems are often designed and evaluated with system outputs in mind: the quality of answers, the number of votes, the accuracy of content created. In this proposal, we review literature on the design values of "citizen-x” systems, put forward a series of models for describing the civic values in “citizen-x," and classify systems by those models. We conclude by urging greater attentiveness to civic values when designing and evaluating human computation and collective action systems.